IMPLEMENTASI RAHMATAN LIL ‘ALAMIN PERSPEKTIF KH. HASYIM MUZADI DI MADRASAH - Rosidi, Rosidi (STAI Ma'had Aly Al-Hikam Malang, 2020)
Abstract: Islam is a religion which has been perfecting celestial religions, and teaching about the importance of love and peace. KH. Hasyim Muzadi was among one of the national figures after the reformation and tragedy of the WTC 11 // 2011 in America who consistently campaigned for the teachings of Islam by carrying